Biblical Allusions in Steinbeck’s The Grapes of Wrath - Shayma' Abdul Ali Jasim (PROSPECTIVE RESEARCHES, 2023)
It is no accident that many characters and events in Steinbeck's The Grapes of Wrath reflect historical, religious and mythological figures. That is exactly what this study tries to prove. For example, there are certain Biblical references in the title of the novel itself. There are also many parallels to the Bible, for instance, Jim Casy has the same initials as Jesus Christ, and he travels to California with twelve people (a migration toward sort of Eden, like when Moses led his people out of Egypt). Christ had twelve apostles. Casy scarifies himself for Tom, and gives up his life willingly to help the lives of others. There are other parallels to Noah and Virgin Mary. Also, there is an indication to the Exodus journey which is reflected and paralleled by the journey to California.